2022
DOI: 10.3389/fendo.2022.1046159
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomic analysis in patients with Hashimoto’s thyroiditis

Abstract: BackgroundHashimoto’s thyroiditis, an autoimmune thyroid disease, shows high morbidity worldwide, particularly in female. Patients with Hashimoto’s thyroiditis have an increasing risk of hypothyroidism during the occurrence and progression of Hashimoto’s thyroiditis. In recent years, metabolomics has been widely applied in autoimmune diseases, especially thyroid disorders. However, metabolites analysis in Hashimoto’s thyroiditis is still absent.MethodsA total of 92 samples were collected, including 35 cases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Lu et al (46), in H 1 NMR analysis of plasma from papillary thyroid microcarcinoma patients, reported reduced levels of valine, lysine and leucine compared with healthy groups. In a study by Jiang et al (41), valine, leucine, and isoleucine degradation and valine, leucine, and isoleucine biosynthesis differentiated euthyroid HT patients from HT patients with subclinical hypothyroidism. However, it should be stressed that Hashimoto disease may influence the metabolism of many other tissues, and this may affect serum AA concentrations.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Lu et al (46), in H 1 NMR analysis of plasma from papillary thyroid microcarcinoma patients, reported reduced levels of valine, lysine and leucine compared with healthy groups. In a study by Jiang et al (41), valine, leucine, and isoleucine degradation and valine, leucine, and isoleucine biosynthesis differentiated euthyroid HT patients from HT patients with subclinical hypothyroidism. However, it should be stressed that Hashimoto disease may influence the metabolism of many other tissues, and this may affect serum AA concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…Lysine affects the production of proteins in muscles and bones, and lysine deficiency causes chronic fatigue, irritability, hair loss, anemia, susceptibility to infection, recurrent herpes and metabolic disorders. Jiang et al (41) studied the serum of HT patients and showed that lysine degradation pathways had an impact on different clinical stages of HT (41). Additionally, lysine was increased in the serum of HT and Graves' disease patients (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The contents of arginine and serine involved in the aminoacyl tRNA biosynthesis pathway may be significantly elevated in PTC tissues in the context of HT [ 30 , 32 ]. And, in Jiang's study [ 33 ], Kyoto Encyclopedia of Genes and Genomes Enrichment analysis showed that fatty acid degradation, Arginine, and proline metabolism have a significant impact on HT group compared to normal group.…”
Section: Discussionmentioning
confidence: 99%